A influência das rotas de escassez de renda na atitude ao endividamento : um modelo de mediação-moderada - Carvalho, Bianca Pinto (2022)
Periods of economic recession directly reflect the levels of unemployment, default and indebtedness of the population. Thus, understanding behavioral factors, such as the way individuals face periods of shortage of income, can be decisive to explain financial behaviors and their relationships. In this context, the present study aims to analyze the mediating effect of frugality and impulsiveness moderated by positive affect in the relationship between income scarcity and attitude towards indebtedness and its effect on financial well-being. To this end, a survey was carried out with 148 individuals who had a shortage of income during the pandemic period. Afterwards, the data were analyzed using a set of techniques associated with Structural Equation Modeling (SEM) with the PLS-SEM approach to test nine proposed hypotheses. The results show that income scarcity, frugality and impulsiveness have significant direct effects on the attitude towards indebtedness. Frugality and impulsiveness play a mediating role in the relationship between scarcity of income and attitude towards indebtedness, being moderated by positive affect. Thus, it can be inferred that if, on the one hand, the scarcity of income is high and the positive affect is low, the individual has a lower trait of frugality and greater tendencies of impulsiveness. When income scarcity is high and positive affect is high, the individual is considered more frugal and ends up showing less impulsive behavior. In addition, the attitude towards indebtedness had a negative effect on the present and future dimensions of financial well-being. The findings provide a reflection on the importance of financial well-being for individuals, as well as the promotion of financial education and behavioral factors to face times of economic recession and financial difficulties. The study contributes to a better understanding of the explanatory mechanisms in the relationship between scarcity of income and attitude towards indebtedness.